Genetic characterization of fluoroquinolone resistant Escherichia coli from urban streams and municipal and hospital effluents - Varela, Ana Rita (2016)
Escherichia coli with reduced susceptibility to ciprofloxacin, isolated from urban streams, wastewater treatment plants and hospital effluent between 2004 and 2012, were compared based on multilocus sequence typing (MLST), quinolone and beta-lactam resistance determinants and plasmid replicon type. Isolates from the different types of water and isolation dates clustered together, suggesting the persistence and capacity to propagate across distinct aquatic environments. Escherichia coli with reduced susceptibility to ciprofloxacin, isolated from urban streams, wastewater treatment plants and hospital effluent between 2004 and 2012, were compared based on multilocus sequence typing (MLST), quinolone and beta-lactam resistance determinants and plasmid replicon type. Isolates from the different types of water and isolation dates clustered together, suggesting the persistence and capacity to propagate across distinct aquatic environments. The most prevalent MLST groups were ST10 complex and ST131. Almost all isolates (98%) carried mutations in the chromosomal genes gyrA and/or parC, and 10% possessed the genes qepA, aac(6')-Ib-cr and/or qnrS1. Over 80% of the isolates were resistant to three or more classes of antibiotics (MDR ≤3). The most prevalent beta-lactamase encoding gene was blaTEM, followed by blaCTX-M-15, co-existing with plasmid mediated quinolone resistance. The plasmid replicon types of the group IncF were the most prevalent and distributed by different MLST groups. The genes aac(6')-Ib-cr and/or qnrS1 could be transferred by conjugation in combination with the genes blaTEM,blaSHV-12 or blaOXA-1 and the plasmid replicon types I1-Iγ, K, HI2 and/or B/O. The potential of multidrug resistant E. coli with reduced susceptibility to ciprofloxacin, harboring mobile genetic elements and with ability to conjugate and transfer resistance genes, to spread and persist across different aquatic environments was demonstrated.